2017
DOI: 10.18203/2349-2902.isj20172774
|View full text |Cite
|
Sign up to set email alerts
|

Role of eosinophil count and neutrophil: lymphocyte count ratio as prognostic markers in patients with sepsis

Abstract: Background: Several biomarkers, such as C-reactive protein (CRP) and Procalcitonin have been used to indicate bacterial infection in sepsis. They have limited sensitivity and specificity with high cost, placing them practically out of reach for poor patients in developing countries like India. Hence the need to evaluate eosinophil count and neutrophil-lymphocyte count ratio (NLCR) as an indicator of sepsis considering their lower cost and easier accessibility. The present study was done to establish that eosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The findings of the Abidi et al (36) study were (80% sensitivity and 80% specificity) for cutoff value 40cells/cu.mm.Anotherprospective observational study byHota and Reddy (38) consisting of 50 patients with SIRS and sepsis on admission were studied. They found that eosinophil count was an effective prognostic marker of sepsis with low cost.The cut off value was taken as 40cells/cu.mm.…”
Section: Fig 6: Roc Curve For Eosinophil Count For Mortality Predictmentioning
confidence: 99%
“…The findings of the Abidi et al (36) study were (80% sensitivity and 80% specificity) for cutoff value 40cells/cu.mm.Anotherprospective observational study byHota and Reddy (38) consisting of 50 patients with SIRS and sepsis on admission were studied. They found that eosinophil count was an effective prognostic marker of sepsis with low cost.The cut off value was taken as 40cells/cu.mm.…”
Section: Fig 6: Roc Curve For Eosinophil Count For Mortality Predictmentioning
confidence: 99%